How Santa lost his job - Krensky, Stephen (Simon & Schuster Books for Young Readers, 2001)
Frustrated by Santa's slowness at Christmastime, Muckle the elf creates a mechanical replacement called the Deliverator and proposes a series of contests to prove that it can do Santa's job better than he can.